Explainable Feature Engineering for Multi-class Money Laundering Classification - Petre-Cornel GRIGORESCU; Antoaneta AMZA (Informatică economică)
This paper provides insight into typical money laundering typologies used in the financial crime domain and provides a concrete set of methods through the use of which fraudulent transactions may be classified using traditional machine learning algorithms and proving the efficacy of tree-based models in not only predictive power, but also explainability and ease of interpretation of results.